2001
DOI: 10.1080/089106001750071690
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Distribution of Bifidobacterial and Enterobacterial Species in Human Faecal Microflora of Three Different (Children, Adults, Elderly) Age Groups

Abstract: To determine if there is any change with age in the distribution of Bi dobacterium and Enterobacteriaceae species in human intestinal micro ora, strains were isolated from a total of 54 samples of human faeces (15 children, 3-15 years old; 17 adults, 30-46 years old; 22 elderly, 69-89 years old). The bi dobacteria were identi ed at species level using a numerical phenotypic identi cation system developed on the Internet (http:::kounou.lille.inra.fr) and DNA-DNA hyridization. The enterobacteria were identi ed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 27 publications
10
74
3
5
Order By: Relevance
“…infantis) were frequently found in feces from breast-fed infants, suggesting that these three species play a crucial role in gut colonization (16,30,39). In accordance with previous studies (15,37,38), B. longum was the most common species in human adult feces, followed by B. adolescentis, B. bifidum, and B. pseudocatenulatum. A high incidence of B. longum, B. adolescentis, B. bifidum, and members of the B. catenulatum group was observed in Japanese adults (29,30).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…infantis) were frequently found in feces from breast-fed infants, suggesting that these three species play a crucial role in gut colonization (16,30,39). In accordance with previous studies (15,37,38), B. longum was the most common species in human adult feces, followed by B. adolescentis, B. bifidum, and B. pseudocatenulatum. A high incidence of B. longum, B. adolescentis, B. bifidum, and members of the B. catenulatum group was observed in Japanese adults (29,30).…”
Section: Discussionsupporting
confidence: 86%
“…At 2 years of age, when the complex gut microbiota is fully established, the proportion of fecal bifidobacteria decreases to 1 to 3% (41). Even lower levels or absence of bifidobacteria have been reported for the elderly (3,15,19,38).…”
mentioning
confidence: 99%
“…In addition, increasing evidence suggests that aging is associated with alterations in the gut microbiota (Bartosch et al 2004;Biagi et al 2010;Gavini et al 2001;Hopkins et al 2001;Hopkins and Macfarlane 2002;Mueller et al 2006;Woodmansey et al 2004). Moreover, elderly subjects living in hospitals and nursing homes are susceptible to increased pathogen challenges.…”
Section: Introductionmentioning
confidence: 99%
“…According to API identification these isolates were classified as Bifidobacterium spp., B. longum or B. bifidum . This is in contrast with most previous studies on the specific composition of bifidobacteria within the elderly, where B. adolescentis was reported as the most common Bifidobacterium species (11,33,34). However, these studies relied upon phenotypic identification techniques and not 16S rDNA sequencing.…”
Section: Resultsmentioning
confidence: 65%
“…Gavini et al (11) determined the changes in the Bifidobacterium species by DNA Á/DNA hybridization in three different age groups and concluded that B. adolescentis was the most frequently isolated species in the 22 elderly subjects examined, whereas B. longum was the most frequently encountered species from 15 children and 17 adults. Using microbial culture techniques combined with molecular typing, Kimura et al (35) observed that each of the 10 human subjects studied harboured a unique collection of bifidobacteria and lactobacilli, at least for the numerically predominant strains.…”
Section: Discussionmentioning
confidence: 99%